A story about villains, alkenes and mining. Management of socio-environmental conflicts in the basin of Jequetepeque - Montoya Canchis, Luis (2017)
The work systematizes the experience of management socio-environmental conflicts in the upper basin of Jequetepeque particularly in the Province of St. Paul of the Cajamarca Region, by the Group of Formation and Intervention for Sustainable Development (GRUFIDES) in partnership with Enginyeria Sense Fronteres (ESF). The main purpose of this initiative was to design and validate tools for environmental governance at the municipal level to enable the promotion the active participation of the population. The prospect of intervention was a watershed approach. One of the most obvious tensions emerging from the experience, and may be-come a crucial point for new investigations and experiences of intervention in the future, is that the formation of consensus building spaces and inclusive spaces of co-management at the local level, not necessarily are conciled with the processes of mobilization and citizen participation autonomous, especially of indig enous peasant roots and located in contexts of activity extractive industries.